THE IMPACT OF INTERNAL AUDIT ON THE OPERATIONAL FINANCING TRANSACTIONS OF THE COMPANY PT. JASA RAHARJA (PERSERO) SURABAYA REPRESENTATIVE - Almadinda Violita Sarajivo; Abdul Hamid; Agus Sumarnadi Nugroho (Media Mahardhika, 2022)
The purpose of this study was to examine and analyze the influence of individual internal audit on the company's operational financing and its implementation at PT. Jasa Raharja (Persero) representative of Surabaya. The results of the study show that internal audit has a significant positive effect on operational financing. Where the increased internal audit results are evidence of good SOP implementation, it will affect operational control of operational financing. And based on the calculation of the R value of 0.555, this shows that internal audit has an effect of 55.5% on the variability of the company's operational financing.